RESPON BOBOT BADAN AKHIR DAN KARKAS AYAM BROILER TERHADAP SUBSTITUSI SEBAGIAN PAKAN KOMERSIL DENGAN TEPUNG DAUNLAMTORO (Leucaena leucocephala) FERMENTASI : LITERATUR REVIEW - Endah Rita Sulistya Dewi; Atip Nurwahyunani, Septiana Nur Kholifah, Aulia Widiawati Fitriana Dewi, Devany England Filany, Jian (CV. ADIBA AISHA AMIRA, 2024)
Broiler chickens and goats are livestock that serve as a source of animal protein. In broiler chickens, productivity is directly proportional to the availability of high-quality feed. Similarly, for goats, feed issues are crucial as they influence carcass composition, particularly fat content. The application of biotechnology in feed processing, utilizing microorganisms through fermentation, is one solution to ensure the availability of quality feed. In this research, data were extracted from relevant research journals and analyzed using a descriptive-analytical approach. The review results indicate that the fermentation of rice bran and unconventional feed fermentation with Aspergillus niger and Saccharomyces cerevisiae is beneficial for broiler chickens. Meanwhile, the fermentation of cassava leaves and peels serves as an alternative feed for village chickens. The utilization of microorganisms in the fermentation of feed for commercial laying hens includes Rhizopus oligosporus, Trichoderma viride, and their combination. On the other hand, cellulolytic bacteria are beneficial for goat feed